Free comment as a valuable approach to characterize and identify the drivers of liking of high-protein flavored milk drink submitted to ohmic heating. (March 2023) - Rocha, Ramon S.; Mahieu, Benjamin; Tavares Filho, Elson R.; Zacarchenco, Patrícia B.; Freitas, Mônica Q.; Mársico, Eliane T.; Pimentel, Tatiana C.; Esmerino, Erick A.; Cruz, Adriano G.
Graphical abstract: Highlights: Sensory characterization of flavored milk processed by ohmic heating using Free-comment. Lower electric fields are associated to a bitter taste and the presence of lumps. Higher electric field strength preserves the attributes of fresh milk. Abstract: Flavored milk drink is a popular dairy product traditionally processed by pasteurization, which is a safe and robust process. Still, it can imply a greater energy expenditure and a more significant sensorial alteration. Ohmic heating (OH) has been proposed as an alternative to dairy processing, including flavored milk drink. However, its impact on sensory characteristics needs to be evidenced. This study used Free Comment, an underexplored methodology in sensory studies, to characterize five samples of high-protein vanilla-flavored milk drink: PAST (conventional pasteurization 72 °C/15 s); OH6 (ohmic heating at 5.22 V/cm); OH8 (ohmic heating at 6.96 V/cm); OH10 (ohmic heating at 8.70 V/cm), and OH12 (ohmic heating at 10.43 V/cm). Free Comment raised similar descriptors to those found in studies that used more consolidated descriptive methods. The employed statistical approach allowed observation that pasteurization and OH treatment have different effects on the sensory profile of products, and the electrical field strength of OH also has a significant impact. PAST was slightly to moderately negatively associated with "acid taste, " "fresh milk taste, " "smoothness, " "sweet taste, " "vanilla flavor, " "vanilla aroma, " "viscous, " and "white color." On the other hand, OH processing with more intense electric fields (OH10 and OH12) produced flavored milk drinks strongly associated with the "in natura" milk descriptors ("fresh milk aroma" and "fresh milk taste"). Furthermore, the products were characterized by the descriptors "homogeneous, " "sweet aroma, " "sweet taste, " "vanilla aroma, " "white color, " "vanilla taste, " and "smoothness." In parallel, less intense electric fields (OH6 and OH8) produced samples more associated with a bitter taste, viscosity, and lumps presence. Sweet taste and fresh milk taste were the drivers of liking. In conclusion, OH with more intense electric fields (OH10 and OH12) was promising in flavored milk drink processing. Furthermore, the free comment was a valuable approach to characterize and identify the drivers of liking of high-protein flavored milk drink submitted to OH.